Effect of Exercise Training on Oxidized LDL-Mediated Platelet Function in Rats - Wang, Jong Shyan; Chow, Shu-Er; Chen, Jan-Kan; Wong, May-Kuen (Thrombosis and Haemostasis, 2000)
This study investigates how exercise training affects Oxidized LDL (Ox-LDL) mediated-platelet activation. Five-week-old male Wistar rats were assigned to either control or trained groups. Trained rats were treadmill-trained for 10 weeks after familiarization. The following measurements were taken in both control and trained groups: Ox-LDLmediated platelet aggregability and [Ca2+]i, plasma and plateletderived nitric oxide (NO) metabolite (nitrite plus nitrate) levels, and antiaggregating activity of NO derived from endothelial cells. Based on those measurements, major findings in this study can be summarized as follows: 1) the trained group had a higher plasma -NO metabolite level than the control group; 2) the trained group had a lower platelet aggregability and [Ca2+]i elevation and a higher platelet derived-NO metabolite level than the control group; 3) the trained group had lower Ox-LDL-potentiated platelet aggregability and [Ca2+]i elevation and Ox-LDL-attenuated NO metabolite in platelet than the control group; 4) treating the platelet with L-arginine inhibited Ox-LDL-potentiated platelet activation in both control and trained groups; 5) Ox-LDL enhances platelet aggregation directly although impairing NO bioactivity but not guanylate cyclase activity in both control and trained groups. Results in this study demonstrate that exercise training decreases Ox-LDL-potentiated platelet activation most likely by enhancing platelet-derived NO release.
Keywords: Exercise training; platelet; nitric oxide; Ox-LDL